Improving Employee Voice About Transgressive or Disruptive Behavior: A Case Study. (April 2019) - Dixon-Woods, Mary; Campbell, Anne; Martin, Graham; Willars, Janet; Tarrant, Carolyn; Aveling, Emma-Louise; Sutcliffe, Kathleen; Clements, Janice; Carlstrom, Michelle; Pronovost, Peter
Abstract : Purpose: Employee voice plays an important role in organizational intelligence about patient safety hazards and other influences on quality of patient care. The authors report a case study of an academic medical center that aimed to understand barriers to voice and make improvements in identifying and responding to transgressive or disruptive behaviors. Method: The case study focused on an improvement effort at Johns Hopkins Medicine that sought to improve employee voice using a two-phase approach of diagnosis and intervention. Confidential interviews with 67 individuals (20 senior leaders, 47 frontline personnel) were conducted during 2014 to diagnose causes of employee reluctance to give voice about behavioral concerns. A structured intervention program to encourage voice was implemented, 2014–2016, in response to the findings. Results: The diagnostic interviews identified gaps between espoused policies of encouraging employee voice and what happened in practice. A culture of fear pervaded the organization that, together with widespread perceptions of futility, inhibited personnel from speaking up about concerns. The intervention phase involved four actions: sharing the interview findings; coordinating and formalizing mechanisms for identifying and dealing with disruptive behavior; training leaders in encouraging voice; and building capacity for difficult conversations. Conclusions: The problems of giving voice are widely known across the organizational literature but are difficult to address. This case study offers an approach that includes diagnostic and intervention phases that may be helpful in remaking norms, facilitating employee voice, and improving organizational response. It highlights specific actions that are available for other organizations to adapt and test.